Peningkatan Hasil Belajar IPA Terpadu Melalui Strategi Pembelajaran Prediction Guide - Albumi Hiburan Zandrato (JURNAL GLOBAL EDUKASI, 2022)
Abstract: The problem in this study is the low quality and student learning outcomes in science subjects Class VIII-1 at SMP Negeri 1 Gunungsitoli. This research was implemented at SMP Negeri 1 Gunungsitoli. The subjects in this study were 32 students of Class VIII-1, and the object of this study was the application of the Prediction Guide learning model. Data collection techniques using tests, observations, questionnaires, and interviews. The test used is a multiple choice test which is carried out at the end of each cycle. Based on the results of research on improving science learning outcomes through the Prediction Guide type cooperative learning model at SMP Negeri 1 Gunungsitoli in cycle I, it was found that the average percentage of student activity was 51.27% in the sufficient category and the success indicator had not yet reached 70%. This can be seen from the percentage of students who asked 46.15% of students who paid attention to the teacher 53.84%, students who wrote key words 58.84%. While the learning outcomes in cycle II, student activity increased with an average percentage of 76.91%. Students who ask 69.22%, students who pay attention to the teacher 76.92%, students who write down key words 84.61%. Student activity in cycle II has reached an indicator of success, which has exceeded 70%.Keywords: prediction guide: prediction Abstak: Permasalahan dalam penelitian ini adalah rendahnya kualitas dan hasil belajar siswa pada mata pelajaran IPA Kelas VIII-1 SMP Negeri 1 Gunungsitoli. Penelitian ini diterapkan di SMP Negeri 1 Gunungsitoli. Subjek dalam penelitian ini adalah siswa Kelas VIII-1 dengan jumlah 32 orang, dan objek dalam penelitian ini adalah penerapan model pembelajaran Prediction Guide. Teknik pengumpulan data menggunakan tes, observasi, angket, dan wawancara. Tes yang digunakan adalah tes pilihan ganda yang dilaksanakan setiap akhir siklus. Berdasarkan hasil penelitian peningkatan hasil belajar IPA melalui model pembelajaran kooperatif tipe Prediction Guide di SMP Negeri 1 Gunungsitoli pada siklus I didapat rata-rata presentase aktivitas siswa 51,27% dalam kategori cukup dan belum mencapai indikator keberhasilan 70%. Hal ini dapat dilihat dari persentase siswa yang bertanya 46,15% siswa yang mau memperhatikan guru 53,84%, siswa yang menuliskan kata-kata kunci 58,84%. Sedangkan hasil belajar pada siklus II, aktivitas siswa meningkat dengan presentase rata-rata 76,91%. Siswa yang bertanya 69,22%, siswa yang memperhatikan guru 76,92%, siswa yang menuliskan kata-kata kunci 84,61%. Aktivitas siswa pada siklus II sudah mencapai indikator keberhasilan yaitu sudah melebihi 70%.Kata kunci: prediction guide: prediksi